The Use of Kaolin West Kalimantan as an Extender Pigment In The Manufacture of Emulsion Paint - Lusiana, Uray; Cahyanto, Heru Agus (Balai Riset dan Standardisasi Industri Pontianak, 2014)
Wall paint emulsion is an emulsion of a mixture of pigments, binders and solvents, and other additives that are used primarily for painting walls. This study was conducted to determine the use of kaolin as a extender pigment West Kalimantan in the manufacture of emulsion paint walls. Kaolin is used combined with titanium dioxide with a percentage of 33% , 42% , 50% , 58% and 67% of the total pigment . The best results are obtained on the addition of 50% kaolin with power caps 29m2/L, density 1.40 g/cm3, fineness of 25microns, dry touch 10 seconds, hard dry 20 minutes, 61.99 wt% total solids, pH 7.21, viscosity 107 KU, resistance to alkali and accelerated weather for 600 hours. This was the best result and has met the quality requirements SNI 3564:2009 of emulsion paint.